Comparison Study of the Effect of Erlotinib as a Tyrosine Kinase Inhibitor on Electrolyte Levels in Type2 Diabetic and Diabetic Nephropathy - Al-Khdhairi, Zainab Mahdi Abed; Ali, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Diabetes mellitus can be defined as  a metabolic disorder disease .Complication  of diabetes  are due to diabetic nephropathy .This study was done in vitro to study the effect of different concentrations of erlotinib inhibitor ( tyrosine kinase inhibitor) on electrolyte levels (MgâºÂ²,CaâºÂ²,Naâº) in sera of Iraqi patients with  newly diagnosis type2 diabetes and diabetic nephropathy in addition to find the best percentage inhibition for utilizing different concentrations from erlotinib (6.97x10â»â·, 9.30x10â»â· ,1.16x10â»â¶,1.39x10â»â¶ ,1.62x10â»âµ )molar  on electrolyte levels . This study was conducted in The National Diabetes Center, Al-Mustansiriya University - Baghdad and included 150 patients divided into50 patients type 2 diabetic as group (G2) , 50patients diabetic nephropathy as group(G3) and also 50 healthy as control group(G1).The period time for aggregation the blood sampling  was from July to October 2017 . All patients were within (18 to 60) years age. Erlotinib(Tyrosine kinase  inhibitor) affected  on serum Mg âºÂ²levels in human as a mild effect and a slight effect on seum Naâº and CaâºÂ².The best inhibition of erlotinib in concentration (1.62x10â»5)M for both  serum Naâº and CaâºÂ² in newly diagnosis diabetes type 2 and diabetic nephropathy.serum  Mg âºÂ²levels showed best inhibition in  concentration (9.30x10â»7)M